A SEMIOTIC-ANALYSIS BASED ON PEIRCE TRIADIC THEORY ON TAGLINES OF NOKIA, HONDA, AIRASIA, LG AND YOU C 1000 ADVERTISING - Fenti Mariska Yohana (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2015)
This analysis is to describe the signs on taglines of Nokia, Honda, Airasia, LG, and YOU C 1000 advertising. The aim is to find out the relation among the signs of the representament, interpretant, and object in Peirce theory. In order to grasp the taglines, a semiotic-analysis triadic theory approach is needed to analysis the taglines. This qualitative approach can determine by perspective of writer to represent the taglines in these advertising. It can be conclude that triadic theory is needed to reveal how the taglines can make sure the viewers, listeners, and audiences to make a competitive campaign.Keywords : Sign, Advertising, Tagline